Upaya Pasangan Long Distance Marriage (LDM) Dalam Menjaga Ketahanan Keluarganya Di Desa Darungan Rambipuji - Khalisa Adila; Robby Sofyan Iskandar; Muhamad Ridawan Arif; Alfisyah Nurhayati (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Long Distance Marriage in Indonesia is something that is no longer foreign to the people, because many married couples in Indonesia choose to emigrate and even go abroad to make ends meet. According to the National Agency for Placement and Protection of Indonesian Workers (BNP2TKI) 2018, in Indonesia the number of TKI in 2014 reached 429,874 of which 48% were male and 57% female, whereas in 2015 there were 275,737 of whom were male and 40% were female. 60%, in 2016 the number of migrant workers reached 234,451 of which the percentage was male 38% female 62%, in 2017 the number was 262,899 of which male 30% female 70%. And in 2018 the number of migrant workers reached 283,640 men 30% women 70%. This research method uses a qualitative research method with a descriptive approach. Research is carried out by collecting data expressed in words or verbally. This research focuses on families undergoing LDM relationships. Therefore, this research focuses on harmony and wholeness for families in LDM relationships. In this research, the data collection process was carried out using interview techniques. Long Distance Marriage where a husband and wife do not live in the same house, as we know the husband has an inner and outer support for his wife but when they undergo LDM this income will not be fulfilled in general, but this does not make this couple give up on the family The efforts they have made to ensure that their household is safe and peaceful despite the distance separating them are: 1. Understanding each other towards their partner 2. Being honest with their partner 3. Accepting each other 4. Being able to control each other's emotions 5. Trusting each other 6. Maintain commitment.